Microbially-Aided SiO2 Biomineralization - Amores, Roderick (My University, 2008)
Microorganisms inhabiting silica solute-rich environments often show various degrees of Si02 mineralization as a consequence of exposure to SiOrsaturated waters. As such, it has been thought that microorganisms exert a prominent role in the immobilization of amorphous silica phases. While this intimate spatial relationship of microorganisms and amorphous Si02 phases are almost always observed in hot springs, the exact mechanisms by which microbes affect Si02 secondary mineral precipitation is still poorly understood. Further, available laboratory investigations to date consistently showed that microbes do not significantly impact Si02 immobilization, suggesting that microbial silicification is a mere consequence of exposure to a largely abiogenically-driven Si02 precipitation.
This study demonstrates that discernible microbially-mediated silicification can occur under conditions where the potential for microbial opportunity to biomineralize is promoted. Identification of the key geochemical requirements for biosilicification to occur include thermodynamically favorable, but sluggish silica reaction kinetics associated with acidic conditions, and the necessity for colloidal silica rather than dissolved silicic acid species. This work provides the first results to bridge the apparent literature discrepancy between widespread, in-situ observations of microbial silicification, and the inability to demonstrate a detectable microbial effect in this process under well-constrained laboratory conditions.
Acid conditions promote microbial silicification by overriding the dominant repulsive forces arising from charge similarities between Si02 and cell surfaces, via neutralization of deprotonated surface silanol and carboxylic groups, respectively. Mechanistic consideration for Si02 coordination to cell surfaces suggests direct chemical bonding of silanol to carboxylic groups forming stable inner-sphere complexes largely insensitive to environmental perturbations. This result indicates that microbially immobilized Si02 are more tenaciously-coordinated on cell surfaces and not simply electrostatically-held.
Surface-dependent silicification showed higher Si02 mineralization propensities for unmineralized microbial cells compared to silica-encrusted cell matrices. Moreover, the extent and style of microbial Si02 mineralization is impacted by cellular level of metabolic activity. These results suggest that a biological overlay may be discernible in microbially induced biosilicification.
Keywords: microbial silification; biomineralize; silica reaction